Kebijakan Komisi Pemilihan Umum dalam Pembentukan Badan Ad Hoc Penyelenggara Pemilu yang Berkualitas - Putri Zaeicha Rahmawanti; Indra Aditya; Lina Aryani (T JDP (JURNAL DINAMIKA PEMERINTAHAN), 2026)
The ad hoc bodies, as the main actors in the stages of elections, require significant attention. The 2019 General Election in Indonesia left numerous issues that needed to be addressed in preparation for the 2024 election. Problems such as the deaths of Polling Station Working Committee (KPPS) officers and frequent violations during election stages involving ad hoc bodies must be minimized. During the 2020 Regional Head Election (Pilkada), other challenges emerged regarding the fulfillment of ad hoc recruitment quotas, where several regions required extensions to complete the recruitment process. Therefore, a policy from the General Elections Commission (KPU) as the election organizer is essential. The KPU issued a policy stipulated in Regulation No. 8 of 2022 concerning the Formation and Working Procedures of Ad Hoc Election and Regional Head Election Organizing Bodies. This study employs a descriptive analytical method with data collection conducted through a literature review of various relevant sources. The findings indicate that the KPU’s policy aims to meet the need for competent and high-quality ad hoc bodies in ensuring credible elections.